2022
DOI: 10.3201/eid2809.220634
|View full text |Cite
|
Sign up to set email alerts
|

Ancylostoma ceylanicum Hookworms in Dogs, Grenada, West Indies

Abstract: Ancylostoma ceylanicum hookworms are recognized agents of human infection in the Asia–Pacific region. We investigated prevalence of zoonotic hookworm infections in dogs in Grenada in 2021; 40.8% were infected by hookworms, including Ancylostoma ceylanicum . Surveillance of this parasite in dogs and humans is needed in tropical/subtropical countries in the Americas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
(39 reference statements)
0
7
0
Order By: Relevance
“… 16 , 19 , 23 25 All three species of hookworms infecting humans are globally distributed, including A. ceylanicum , which has been described in Asia, Oceania, Africa, 2 , 26 , 27 and more recently the Americas. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 19 , 23 25 All three species of hookworms infecting humans are globally distributed, including A. ceylanicum , which has been described in Asia, Oceania, Africa, 2 , 26 , 27 and more recently the Americas. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Autochthonous infections with A. ceylanicum in the Americas have only recently been described in humans in Ecuador 4 and dogs in Grenada in the Caribbean. 5 …”
Section: Introductionmentioning
confidence: 99%
“…First, while being most common in Southeast Asia and the Pacific, the geographic extent of A. ceylanicum continues to expand with the increasing use of molecular methods that distinguish hookworm species. Indeed, A. ceylanicum has recently been identified for the first time in the Americas ( 52 , 53 ). Second, diagnosis and geographical mapping relies on molecular PCR methods which are more costly and resource-intensive than traditional parasitological methods.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, a recent study of wild dogs (dingoes and dingo hybrids) in periurban areas of northern Australia found that up to 100% were infected with A. ceylanicum thus constituting a zoonotic risk to communities in this tropical area of northern Australia (Smout et al, 2013). Most recently, molecular tools have confirmed the presence of A. ceylanicum in the West Indies and South America (Sears et al, 2022;Zendejas-Heredia et al, 2022). In many areas where hookworm is endemic, dogs are common in villages and communities where a number of hookworm species may coexist in humans and dogs.…”
Section: Epidemiologyunderstanding Transmissionmentioning
confidence: 99%